Sublingual immunotherapy for the treatment of allergies - Natalie Schellack; D. Engler (South African Family Practice)
The treatment of allergies often involves pharmacological therapy and recommendations by healthcare workers that the allergen should be avoided. Allergen-specific immunotherapy has emerged as an alternative to effectively decrease the immunoglobulin (Ig) E:IgG4 ratio. Two routes of administration are described, namely subcutaneous immunotherapy, which has always been considered to be the gold standard of treatment, and sublingual immunotherapy, which has recently been shown to have fewer systemic side-effects and improved compliance by patients.